Oxygen-vacancy-rich Ru-clusters decorated Co/Ce oxides modifying ZIF-67 nanocubes as a high-efficient catalyst for NaBH4 hydrolysis. (1st November 2022) - Shi, Luyan; Zhu, Ke; Yang, Yuting; Liu, Yi; Xu, Shoulei; Isimjan, Tayirjan Taylor; Yang, Xiulin
Abstract: Designing a cost-effective and high-performance catalyst for NaBH4 hydrolysis is a significant step in developing a sustainable hydrogen source. Herein, we prepared a cost-effective Ru-clusters decorated cobalt-cerium oxides coating ZIF-67 (Ru/Co6 Ce1 @ZIF-67) catalyst via a facile reduction method, displaying high performance and exceptional reusability in alkaline NaBH4 solution. The optimized catalyst exhibits a high hydrogen generation rate (HGR, 5726.1 mL min −1 g −1 ), turnover frequency (TOF, 413.9 molH2 min −1 mol R u − 1 ), and low activation energy (Ea, 53.0 kJ mol −1 ), surpassing most of the recently reported catalysts. Furthermore, the catalytic performance does not change considerably after five cycles, indicating the catalyst's multi-cycle reusability. Studies imply the uniquely synergistic effect of Ru, Co/Ce oxides, abundant oxygen vacancies, as well as the porous nanocube structure, enabling the catalysts to possess high metal dispersion, outstanding catalytic performance and exceptional reusability. This work will open light on using an oxygen vacancies-rich strategy to design a high-activity catalyst for promoting NaBH4 hydrolysis. Graphical abstract: A highly effective catalyst of Ru/Co6 Ce1 @ZIF-67 is fabricated by a facile surfactant-mediated and chemical reduction methods. Systematic investigations revealed that the designed catalyst processes a high hydrogen generation rate, turnover frequency, as well as multi-cycle reusability in alkaline NaBH4 solution. Image 1 Highlights: Ru/Co6 Ce1 @ZIF-67 nanocubes are fabricated by surfactant-mediated and reduction methods. The catalyst shows a high HGR and TOF (413.9 min −1 ) surpassing most recently reported catalysts. The catalyst exhibits a stable multi-cycle reusability for NaBH4 hydrolysis. Oxygen vacancies and the synergy between different components are the keys to improve catalytic activity.